Evaluating a Single Domain Antibody Targeting Human PD-L1 as a Nuclear Imaging and Therapeutic Agent - Broos, Katrijn (Cancers (Basel), 2019)
The PD-1:PD-L1 immune checkpoint axis is central in the escape of cancer cells from anticancer immune responses. Monoclonal antibodies (mAbs) specific for PD-L1 have been approved for treatment of various cancer types. Although PD-L1 blockade has proven its merit, there are still several aspects that require further attention to fully capitalize on its potential. One of these is the development of antigen-binding moieties that enable PD-L1 diagnosis and therapy. We generated human PD-L1 binding single domain antibodies (sdAbs) and selected sdAb K2, a sdAb with a high affinity for PD-L1, as a lead compound. SPECT/CT imaging in mice following intravenous injection of Technetium-99m ((99m)Tc)-labeled sdAb K2 revealed high signal-to-noise ratios, strong ability to specifically detect PD-L1 in melanoma and breast tumors, and relatively low kidney retention, which is a unique property for radiolabeled sdAbs. We further showed using surface plasmon resonance that sdAb K2 binds to the same epitope on PD-L1 as the mAb avelumab, and antagonizes PD-1:PD-L1 interactions. Different human cell-based assays corroborated the PD-1:PD-L1 blocking activity, showing enhanced T-cell receptor signaling and tumor cell killing when PD-1(POS) T cells interacted with PD-L1(POS) tumor cells. Taken together, we present sdAb K2, which specifically binds to human PD-L1, as a new diagnostic and therapeutic agent in cancer management.